Stress, Subordination, and Anomalies of Feeding Across the Tree of Life: Implications for Interpreting Human Eating Disorders - Natterson-Horowitz, B.; Cho, Julia H. (Frontiers in Psychology, 2021)
Eating behaviors of animals living in naturalistic environments offer unique insights into several dysregulated eating patterns observed in humans. Social subordination is a known precipitant of hyperphagia and hypophagia in human beings and examples of similar responses have been identified in a phylogenetically widespread range of vertebral species. This points to potentially conserved, patterned responses to animals navigating lives within social hierarchies. Self-imposed food restriction in subordinate fish and hyperphagic responses in socially subordinated bird and primate individuals may represent evolved adaptations to the stress of social subordination. As such, hyperphagic and hypophagic responses to social subordination in these species may model the natural history, neurobiology, and behavioral ecology of human dieting and bingeing more accurately than some current animal models. Phylogenetically widespread similarities in eating patterns under the stress of social subordination point to potentially shared biological benefits of these behaviors across species and the role of evolutionary trade-offs, adaptations, and other processes in shaping them. The application of a broadly comparative lens to disordered eating behaviors in other species exposes important similarities and differences between neurophysiology of eating across species. In doing so, it highlights the value of phylogenetic analyses and macroevolution as tools for identifying novel, naturally occurring models for understanding disordered human eating. Moreover, this approach introduces the intriguing possibility that human cultural influences on disordered eating may have far more ancient origins than previously considered.